Suppression of CHLD gene involved in chlorophyll synthesis in rice using Antisense Oligonucleotides (ASOs) - Nguyễn, Vũ Gia Hân; Nguyễn, Trường Thọ; Ngô, Quốc Nam; Trần, Thanh Mến; Bùi, Thanh Liêm (Hue University Journal of Science: Natural Science, 2026)
Antisense oligonucleotides (ASOs) are emerging as a promising tool for functional genomics research, particularly in the regulation of gene expression. In Viet Nam, however, studies on the application of ASOs in plant systems remains limited. This study aimed to evaluate the effects of ASOs on rice (Oryza sativa) by targeting the CHLD gene, which encodes a subunit of Mg–chelatase involved in chlorophyll biosynthesis. ASOs were synthesized in both unmodified and chemically modified phosphorothioate (PS) forms. Rice seedlings at four days after germination were treated by foliar spraying with ASOs at a concentration of 100 pmol/mL. The effects of ASO treatments were assessed at 3, 7, and 14 days after application based on leaf color, plant morphology, plant height, root length, and the contents of chlorophyll a, chlorophyll b, and carotenoids. The results showed that ASO-treated plants exhibited a marked reduction in leaf pigment contents and plant height at 3 and 7 days after treatment. Specifically, chlorophyll a content decreased by 52–72%, chlorophyll b by 47–73%, and carotenoids by 50–71%, while plant height was reduced by 17–32% compared with the control. In contrast, root development was not affected by ASO application. These findings demonstrate that ASOs can effectively suppress CHLD gene–associated phenotypes, highlighting their potential as a tool for gene expression control and functional gene analysis in crop plants.